Anticoagulation Use and Clinical Outcomes After Major Bleeding on Dabigatran or Warfarin in Atrial Fibrillation. Issue 1 (January 2017) - Hernandez, Inmaculada; Zhang, Yuting; Brooks, Maria M.; Chin, Paul K.L.; Saba, Samir
Abstract : Background and Purpose—: Little is known about the clinical outcomes associated with posthemorrhage anticoagulation resumption for atrial fibrillation. This study had 2 objectives: first, to evaluate anticoagulation use after a first major bleed on warfarin or dabigatran and, second, to compare effectiveness and safety outcomes between patients discontinuing anticoagulation after a major bleed and patients restarting warfarin or dabigatran. Methods—: Using 2010 to 2012 Medicare Part D data, we identified atrial fibrillation patients who experienced a major bleeding event while using warfarin (n=1135) or dabigatran (n=404) and categorized them by their posthemorrhage use of anticoagulation. We followed them until an ischemic stroke, recurrent hemorrhage, or death through December 31, 2012. We constructed logistic regression models to evaluate factors affecting anticoagulation resumption and Cox proportional hazard models to compare the combined risk of ischemic stroke and all-cause mortality and the risk of recurrent bleeding between treatment groups. Results—: Resumption of anticoagulation with warfarin (hazard ratio [HR] 0.76; 95% confidence interval [CI] 0.59–0.97) or dabigatran (HR 0.66; 95% CI 0.44–0.99) was associated with lower combined risk of ischemic stroke and all-cause mortality than anticoagulation discontinuation. The incidence of recurrent major bleeding was higher for patients prescribed warfarin after the event than for those prescribed dabigatran (HR 2.31; 95% CI 1.19–4.76) or whose anticoagulation ceased (HR 1.56; 95% CI 1.10–2.22), but did not differ between patients restarting dabigatran and those discontinuing anticoagulation (HR 0.65; 95% CI 0.32–1.33). Conclusions—: Dabigatran was associated with a superior benefit/risk ratio than warfarin and anticoagulation discontinuation in the treatment of atrial fibrillation patients who have survived a major bleed. Abstract : Supplemental Digital Content is available in the text.